TRANSFORMASI MUATAN LOKAL DALAM PENGEMBANGAN KURIKULUM PENDIDIKAN DI ACEH - Saifullah Maysa (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
The study of the potential for local content of Acehnese culture in educational institutions can be transformed into a subject of local content and school culture in order to respond to the challenges of the times and frequent curriculum changes. Qualitative research focused on two districts/cities in Aceh province, namely Banda Aceh City and Aceh Besar District. Data collection techniques in this study used three instruments, namely, interview lists, observation sheets, and documentation lists. It was found that a number of local content of Acehnese culture existed in educational institutions that were integrated with school culture, such as; a culture of prayer, a culture of learning, respecting and honoring teachers, infaq and alms within educational institutions, a clean culture, mutual cooperation, commemorating the Islamic Great Day, the Diniyah program at night for boarding schools, entrepreneurship programs (Life Skills). This has shown a transformation of the local content of Acehnese culture which is practiced in all secondary education institutions in Aceh province in order to promote Islamic symbols.